Restructuring Through FDI in Romanian Manufacturing - Gabor Hunya (The Vienna Institute for International Economic Studies (wiiw), 2002)
Romania has experienced a drawn-out transformation process and received relatively low amounts of foreign direct investment (FDI). But it has become competitive in labour-intensive manufacturing industries through the integration into European company networks by processing trade. The country has also achieved economic growth supported by a massive export expansion for the third year running in 2002, after long and deep setbacks. The FDI inflows of the last five years have decisively contributed to the resumption of economic growth and the recovery of exports. But flowing at the current speed and in the current structure, FDI will not be able to restructure the Romanian economy in a way for it to stay on a rapid economic growth path. Despite the low amount of FDI in Romania as compared with the more advanced transition countries, foreign penetration in the manufacturing industry is high. With a database relying on company balance sheets, the performance of foreign affiliates in manufacturing industries was analysed. An important finding is that significant foreign presence in an industry coincides with increasing export performance. Foreign affiliates have so far had a conserving rather than restructuring effect on Romanias foreign trade structure. FDI reinforced Romanias traditional specialization in clothing, footwear and metals. They are also the driving force behind the emergence of exports in the electrical machinery and electronics sector. We can foresee a similar development in the car industry in the future. More success in new export industries was hindered by unfavourable conditions for green-field investments.
Keywords: F14; F21; F23; O14; P21; P27; 330; foreign direct investment; restructuring; foreign investment enterprises; foreign trade; privatization